Issues Of Identity In 21st-Century Selected Australian Jewish Fiction: An Analysis Based On Derridaʼs Concept Of Différance - Badurais, Rasha Saeed Abdullah (2022)
Jewish identity is a prototype of enigma and instability rendered in the unanswered inquiry, “Who is the Jew?” With the postmodern impact, it is increasingly getting fluid and unstable. A factor that intensifies the Jewish identity mosaic nature is their prolonged diaspora. One of the largest and most influential groups is the Anglophone Jewish diaspora of which the Australian Jewish diaspora has been selected as the focus of the present thesis. Since it represents a cosmopolitan context amalgamating features of the West, the USA and the UK, and the east as being close to Asia.